IMPORTANCE OF CITIES AS CENTERS OF ADMINISTRATION (City: History, Culture, Society, 2021)
Ukraine is a unitary state with the administrative and political division is represented by a four-level hierarchy. Let us analyze the main issues of the present-day administrative-territorial structure of Ukraine. Special legal status was the administrative-territorial structure of the territory subordinated to Sevastopol City Council is peculiar. The actual administrative status of towns of oblast subordination Pripyat and Chornobyl (Kyiv oblast) that are located within the exclusion zone is not officially defined. The temporary special legal status of the local government was in force from 2001 up to 2006 urban settlement Kotsiubynske, a part of the Irpin Town Council, passed in subordination to the State administration of the capital – city of Kyiv. Enclavement implies the entire encirclement of an administrative unit by another administrative unit. There is a group of Town Councils that have numerous enclave parts (they are typical for Donbas). The term administrative stripping implies that the territories of administrative units wedge between each other, which is typical mainly for urbanized territories. “Administrative matryoshka” – 64 cities of oblast subordination of Ukraine have 202 other administrative-territorial units in their composition. Numerous conflicts within the system of management are caused by the above-mentioned problems of the administrative and territorial division.
Keywords: city/town; the administrative and political division of State; cities council